Admissions to hospital with exacerbations of chronic obstructive pulmonary disease: effect of age related factors and service organisation. Issue 10 (23rd August 2006) - Connolly, M J; Lowe, D; Anstey, K; Hosker, H S R; Pearson, M G; Roberts, C M
Abstract : Background: Exacerbations of chronic obstructive pulmonary disease (COPD) have a high rate of mortality which gets worse with advancing age. It is unknown whether this is due to age related deficiencies in process of care. A study was undertaken in patients with COPD exacerbations admitted to UK hospitals to assess whether there were age related differences in the process of care that might affect outcome, and whether different models of care affected process and outcome. Methods: 247 hospital units audited activity and outcomes (inpatient death, death within 90 days, length of stay (LOS), readmission within 90 days) for 40 consecutive COPD exacerbation admissions in autumn 2003. Logistic regression methods were used to assess relationships between process and outcome at p<0.001. Results: 7514 patients (36% aged ⩾75 years) were included. Patients aged ⩾75 years were less likely to have blood gases documented, to have FEV1 recorded, or to be given systemic corticosteroids. Those admitted under care of the elderly (CoE) physicians were less likely to enter early discharge schemes or to receive non-invasive ventilation when acidotic. Overall inpatient and 90 day mortality was 7.4% and 15.3%, respectively. Inpatient and 90 day adjusted odds mortality rates for those aged ⩾85 years (versus ⩽65 years) were 3.25 and 2.54, respectively. Mortality was unaffected by admitting physician (CoE v general v respiratory). Age predicted LOS but not readmission. Age related deficiencies in process of care did not predict inpatient or 90 day mortality, readmission, or LOS. Conclusions: Management of COPD exacerbations varies with age in UK hospitals. Inpatient and 90 day mortality is approximately three times higher in very elderly patients with a COPD exacerbation than in younger patients. Age related deficiencies in the process of care were not associated with mortality, but it is likely that they represent poorer quality of care and patient experience. Recommended standards of care should be applied equally to elderly patients with an exacerbation of COPD.